Analisis Keterampilan Menulis Karangan Narasi Siswa Kelas V MI Al Muhajirin - Mursida, Mursida; Azura, Wan; Sari, Ira (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the narrative writing skills of fifth-grade students at MI AL Muhajirin. Writing is an important aspect in Indonesian language learning, especially in the form of narrative writing skills that require students' abilities to organize ideas, structure a story line, and use language appropriately and coherently. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation. The results show that most students experience difficulties in writing narrative essays in their entirety, such as in organizing the story line, developing paragraphs, and using appropriate vocabulary. In addition, deficiencies are also found in linguistic aspects such as spelling, punctuation, and sentence structure